1994
DOI: 10.1038/370151a0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and activation of the Jak-3 Janus kinase in response to interleukin-2

Abstract: Interleukin-2 is an autocrine growth factor for T cells which also activates other cells including B cells and natural killer cells. The subunits of the interleukin-2 receptor (IL-2R) lack intrinsic enzymatic activity, but protein tyrosine phosphorylation is a critical event following ligand binding and src family kinases, such as Lck, are known to be activated by IL-2 (refs 5-9). However, IL-2 signalling can occur in the absence of receptor interaction with Lck, suggesting that other protein tyrosine kinases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
309
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(324 citation statements)
references
References 26 publications
12
309
1
2
Order By: Relevance
“…The Jaks are activated within minutes of IL-2 binding (7,8,17). Jak1 associates with the ILTkaczuk et al (Figure 2A, pJak1 or pJak3).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The Jaks are activated within minutes of IL-2 binding (7,8,17). Jak1 associates with the ILTkaczuk et al (Figure 2A, pJak1 or pJak3).…”
Section: Resultsmentioning
confidence: 90%
“…In this study we evaluated one pathway known to be critical for Tcell proliferation, the Jak/STAT pathway. The janus family of protein tyrosine kinases (Jaks) and signal transducers and activators of transcription (STAT) proteins are rapidly activated upon IL-2R ligation (7,8). Jak1 and Jak3 molecules bind to IL-2Rb and g chain subunits and activate STAT5a/b proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As is typical of type I cytokine receptors, neither IL-2Rb nor g c contains protein kinase activity in its cytoplasmic domain (Hatakeyama et al, 1989;Takeshita et al, 1992). However, within minutes following the interaction of IL-2 with the high-or intermediate-a nity IL-2 receptors, a number of cellular proteins, including IL2Rb and g c , are phosphorylated on tyrosine residues (Farrar and Ferris, 1989;Turner et al, 1991), at least in part by the receptor-associated protein tyrosine kinases, Jak1 and Jak3 (Friedmann et al, 1996;Johnston et al, 1994;Witthuhn et al, 1994). It has been demonstrated that in the absence of IL-2, Jak1 is associated with IL-2Rb Russell et al, 1994;Witthuhn et al, 1994) and Jak3 is with g c Russell et al, 1994;Figure 2).…”
Section: How Does Il-2 Transduce Its Signals?mentioning
confidence: 99%
“…Both cytokines share a pair of receptor subunits, the gamma chain common to several cytokine receptors (γ c , CD132) combined with the IL-2/15 beta receptor chain (IL-2Rβ, CD122) [11]. Binding of either IL-2 or IL-15, with Kd's ~10 −9 M [12, 13,14], will activate this dimeric receptor to transmit intracellular signals via the JAK1/3-STAT3/5 pathways [15,16,17]. There are substantial numbers of these CD122/CD132 receptors on T cells and, at high concentrations (10 −8 M) of either IL-2 or IL-15, these receptors will be saturated.…”
Section: Introductionmentioning
confidence: 99%